2009
DOI: 10.1128/mcb.00105-09
|View full text |Cite
|
Sign up to set email alerts
|

HMGA1 Levels Influence Mitochondrial Function and Mitochondrial DNA Repair Efficiency

Abstract: HMGA chromatin proteins, a family of gene regulatory factors found at only low concentrations in normal cells, are almost universally overexpressed in cancer cells. HMGA proteins are located in the nuclei of normal cells except during the late S/G 2 phases of the cell cycle, when HMGA1, one of the members of the family, reversibly migrates to the mitochondria, where it binds to mitochondrial DNA (mtDNA). In many cancer cells, this controlled shuttling is lost and HMGA1 is found in mitochondria throughout the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 126 publications
(171 reference statements)
1
28
0
Order By: Relevance
“…It has also been demonstrated that over-expression of HMGA1 proteins in cancer cells results in the accumulation of HMGA1 protein in mitochondria [147,148] resulting in the inhibition of BER of oxidative damage in mitochondria DNA (mtDNA) [149]. The mechanisms for repair of lesions in mtDNA are complex and highly dependent on both the type and extent of damage involved but, unlike the nucleus, mitochondria lack the enzymes necessary for NER [150] and thus rely primarily on BER to remove oxidatively damaged bases [151].…”
Section: Base Excision Repairmentioning
confidence: 99%
“…It has also been demonstrated that over-expression of HMGA1 proteins in cancer cells results in the accumulation of HMGA1 protein in mitochondria [147,148] resulting in the inhibition of BER of oxidative damage in mitochondria DNA (mtDNA) [149]. The mechanisms for repair of lesions in mtDNA are complex and highly dependent on both the type and extent of damage involved but, unlike the nucleus, mitochondria lack the enzymes necessary for NER [150] and thus rely primarily on BER to remove oxidatively damaged bases [151].…”
Section: Base Excision Repairmentioning
confidence: 99%
“…It is of interest that several ATM substrates demonstrate mitochondrial translocation (CREB, p53) and affect mitochondrial functions (HMGA1). HMGA1 translocates to mitochondria in the S-G2 phases of cell cycle [232] and levels of HMGA1 are correlated with mitochondrial mass, levels of ROS and repair of mtDNA damage. The role of ATM-dependent phosphorylation of HMGA1 in the mitochondrial biogenesis pathway remains to be explored.…”
Section: Oxidative Stress and Atm Cytoplasmic Signalingmentioning
confidence: 99%
“…These include the utilization of the QPCR method to determine the ability of modulating experimental conditions to influence DNA damage levels or repair in mtDNA or nDNA, such as a 2009 study by Jung et [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. QPCR has also been employed to directly compare mtDNA and nDNA damage in aged tissues [42,43] as well as determine the effects of disease conditions [37,[44][45][46] and conditions such as oxidative stress [31,40] on repair in mtDNA and nDNA.…”
Section: Recent Discoveries Using the Gene-specific Qpcr Assaymentioning
confidence: 99%